Effects of exposure to anti-homosexual humor on individuals' tolerance of and anticipated feelings of compunction about discrimination - Strain, Megan L. (Kansas State University, 2010)
This research examines the effect of exposure to anti-gay humor on individuals’ tolerance of anti-gay discrimination. Participants were exposed to one of four conditions in a 2 (message type; joke or statement) x 2 (disparagement; anti-gay or neutral) design. They read vignettes that contained anti-gay jokes or statements, or neutral jokes or statements. Individuals’ sexual prejudice, humor styles, discrimination tolerance, feelings of compunction, and perceptions of others’ tolerance were also measured. Results showed that individuals exposed to humorous stimuli were more tolerant of discrimination, compared to those exposed to non-humorous stimuli. Further, levels of discrimination tolerance were significantly related both to individuals’ levels of sexual prejudice and their preference for an aggressive humor style. No significant interaction effects were found among these variables. These findings contribute to the literature on disparaging humor by examining its effects on targets of a different social group, and by incorporating humor style as a potential moderating variable.
Keywords: disparagement humor; discrimination; Prejudiced Norm Theory; tolerance; sexual prejudice; humor style; Psychology, Social (0451)